Impact of celebrity endorsement : a study on consumer goods sale - Ramachandran, R. (university of Jaffna, 2014)
In the present era, selling is a complicated task due to stiff competition and many alternative products. Products have become more consumers oriented. Consumers have become more sophisticated. For instance, they posses the best product at a fair price. The products are a better quality than the substitute produce for sale. But Sales aren't automatic. The prior idea of the production is for the sales. How will the buyers get the product, when they have not heard of our products? Therefore, people must have knowledge of the existence of the product and its availability. This is possible only through a good propaganda. It arises a need for proper flow of information along with products from producer to consumer. It can be done through the activity of promotion. Promotion is the process of Marketing Communication aimed to inform, persuade and influence people. It become very essential, rather a duty, of the manufacturers to make the consumers know from where, how, when and at what price the product would be available. More and more promotional activities are required to induce the consumers to purchase more and more products and thus demand for the product is created. The basic purpose of promotion is to let potential customers to know about the product through various forms, roles, models, persons. Thus, the research paper throws light up on current trends in celebrity endorsement and its impact through various models have considered. For the purpose 100 samples on simple random techniques in Tiruchirappalli (Trichy) town and through application of Chi-square test and other methods, it is found that it has major impact in promotion process.
Keywords: Celebrity; Endorsement; Consumer goods; Advertisement; Product; Marketing